The Time-Driven Activity-Based Costing Than Hotel Management Methods For Determining The Cost Of Hotel Room Service? (Case In The Grand Nanggroe Hotel Banda Aceh) - Livya Zahara; Indayani Indayani (Universitas Serang Raya, 2022)
The aims of the research are to analyze the calculation of Time-Driven Activity-Based Costing (TDABC) with the hotel management method to calculate the cost of hotel room services at Grand Nanggroe Hotel Banda Aceh, and the causes of the differences to help the hotel management to determine which method is more efficient. The type of this research is a quantitative descriptive. The strategy is action research. The time horizon is a cross-sectional. The result showed that the cost of hotel room services by TDABC is higher for three type of rooms compared to the management method. This differences cause by the management method that allocated unit costs into one cost driver resulting in lower costs, besides that, the management method did not include facility costs such as labor costs and depreciation costs that related with room division. Furthermore, the result of this research indicates that there is IDR 882,940,385 an unused capacity cost which can be eliminated or maximized by the hotel management.